(untitled) (Biological Sciences - PJSIR, 1998)
Fifteen days old 100chicks were divided into two groups. One group was maintained on standard diet, while the other group was fed on the diet containing 10% rapeseed cake. During 34 weeks of the experiment, rapeseed group was studied for liveability,feed consumption, laying performance andegg quality in comparison with the standard group. No adverse effect was observed rather beneficial effect was observed on the growth and laying performance at this level. Feed consumption for the period of first 6 weeks was 857g chick" for standard group and 918g chick" for rapeseed cake group. Live weight after 20 weeks was 1478.88g pullet:’ for standard group and J 503.07 g puller’ for rapeseed cake group. Laying record of seven weeks showed significant increase (p<0.05) in egg production for rapeseed cake group (72.43%) as compared with 65.58% in standard group. Egg size ranged between 56to 59g in standard group and 54 to 60g in rapeseed cake group. Organoleptic testing revealed no differences in the overall acceptability scores which were 8 in both the cases.